Produção de bebida fermentada a partir de extrato de quinoa (Chenopodium Quinoa Willd) - Silva, Janayna Presa da (2015)
Quinoa is a grain of high nutritional value that has been explored by researchers especially in last years, due to its nutritional characteristics and adaptability of cultivation in areas of restrictive conditions of climate and soil. Production of fermented beverage quinoa based is an alternative food to consumers with food restriction and to those who live in regions where availability of animal protein is scarce. The methodology used to the production of the beverage in this study, can be easily replicated and viable to industrial and artisanal scale. Methodologies used to physic-chemical, microbiological and sensory analysis assessing changes during elaboration of the product and its final quality, following international and national standards analysis.. The time of fermentation ranged between four to six hours to achieve pH 4.6 and final titratable acidity was approximately 1.50%. Due to the action of amylases naturally present at the grain of quinoa and to acidity of the fermented product, the quantity of reducer sugar (RS) increased during the fermentative period. The protein content of developed formulations ranged between 0.50 to 0.69%, these values do not satisfied the expectations. The formulations which were best evaluated on sensory analysis received grades 6.53 to formulation with addition of passion fruit pulp and 6.09 to formulation with addition of passion fruit pulp and carrageenan gum, in relation to the "overall assessment". It can be concluded that production of fermented quinoa based beverage is commercially viable. Beverage quinoa based offers greater variety to individuals who have food allergies or intolerances, or to those that live in situation of food insecurity. However some adjustments during elaboration process are suggested to improve its nutritional contents and sensorial acceptability.